2002
DOI: 10.1029/2001jb000190
|View full text |Cite
|
Sign up to set email alerts
|

Crust and upper mantle discontinuity structure beneath eastern North America

Abstract: [1] Crust and mantle discontinuities across the eastern margin of the North American craton were imaged using P to S converted phase receiver functions recorded by the Missouri to Massachusetts Broadband Seismometer Experiment. Crustal structure constrained by modeling Moho conversions and reverberations shows a variation of Moho depth from a minimum of 30 km near the Atlantic coast to depths of 44-49 km beneath the western Appalachian Province and 38-45 km beneath the Proterozoic terranes in the west. The var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 70 publications
11
61
0
Order By: Relevance
“…The step might represent late Paleozoic differential uplift and exhumation of the orogen (Harrison et al, 1989;Wintsch et al, 2003), or it might reflect changes in crustal thickness due to Mesozoic rifting or underplating (Li et al, 2002). The step might represent late Paleozoic differential uplift and exhumation of the orogen (Harrison et al, 1989;Wintsch et al, 2003), or it might reflect changes in crustal thickness due to Mesozoic rifting or underplating (Li et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The step might represent late Paleozoic differential uplift and exhumation of the orogen (Harrison et al, 1989;Wintsch et al, 2003), or it might reflect changes in crustal thickness due to Mesozoic rifting or underplating (Li et al, 2002). The step might represent late Paleozoic differential uplift and exhumation of the orogen (Harrison et al, 1989;Wintsch et al, 2003), or it might reflect changes in crustal thickness due to Mesozoic rifting or underplating (Li et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Bostock (1996b) found evidence for a weak 220 km discontinuity beneath the Canadian part of the North American craton in P receiver functions. Li et al (2002) found from Ps data a discontinuity at 270-280 km depth beneath eastern North America. Li et al (2002) found from Ps data a discontinuity at 270-280 km depth beneath eastern North America.…”
Section: The Lehmann Discontinuitymentioning
confidence: 92%
“…Interstation spacing was about 100 km and the array operated for about 16 months. Receiver function determinations of crustal thickness along the profile show thickening of the crust beneath the Appalachians, thinning in the region of the Grenville Front and thickening again beneath the stable Proterozoic platform (Li et al, 2002). The root beneath the Appalachians, thicker than predicted for isostatic compensation, appears to reflect a 'densification' of the lower crust that Fischer (2002) had hypothesized is a common metamorphic process in older orogenic belts.…”
Section: Central and Eastern North Americamentioning
confidence: 96%
“…The root beneath the Appalachians, thicker than predicted for isostatic compensation, appears to reflect a 'densification' of the lower crust that Fischer (2002) had hypothesized is a common metamorphic process in older orogenic belts. Upper-mantle discontinuities from receiver functions observed beneath MOMA at depths around 270-280 km are visible in the eastern part of the array and have been interpreted as the (rarely observed) base of the asthenosphere beneath eastern North America (Li et al, 2002). Subsequent studies based primarily on extensive data from a handful of permanent stations in eastern United States suggest that the LAB is sharply defined, perhaps no more than 10-12 km in vertical extend, beneath the Phanerozoic (Rychert et al, 2005).…”
Section: Central and Eastern North Americamentioning
confidence: 96%